A review of 3D concrete printing systems and materials properties: current status and future research prospects. Issue 4 (14th May 2018) - Paul, Suvash Chandra; van Zijl, Gideon P.A.G.; Tan, Ming Jen; Gibson, Ian
Abstract : Purpose: Three-dimensional printing of concrete (3DPC) has a potential for the rapid industrialization of the housing sector, with benefits of reduced construction time due to no formwork requirement, ease of construction of complex geometries, potential high construction quality and reduced waste. Required materials adaption for 3DPC is within reach, as concrete materials technology has reached the point where performance-based specification is possible by specialists. This paper aims to present an overview of the current status of 3DPC for construction, including existing printing methods and material properties required for robustness of 3DPC structures or structural elements. Design/methodology/approach: This paper has presented an overview of three categories of 3DPC systems, namely, gantry, robotic and crane systems. Material compositions as well as fresh and hardened properties of mixes currently used for 3DPC have been elaborated. Findings: This paper presents an overview of the state of the art of 3DPC systems and materials. Research needs, including reinforcement in the form of bars or fibres in the 3D printable cement-based materials, are also addressed. Originality/value: The critical analysis of the 3D concrete printing system and materials described in this review paper is original.